Residential mobility, neighbourhood quality and life-course events - Birgitta Rabe; Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2009)
Neighbourhood characteristics affect the social and economic opportunities of their residents. While a number of studies have analysed housing adjustments at different life stages, little is known about neighbourhood quality adjustments. Based on a model of optimal housing consumption we analyse the determinants of residential mobility and the neighbourhood quality adjustments made by those who move, drawing on data from the British Household Panel Survey and Indices of Multiple Deprivation. We measure neighbourhood quality both subjectively and objectively and find that not all life-course events that trigger moves lead to neighbourhood quality adjustments. Single people are negatively affected by leaving the parental home and couples by a husband s unemployment. Couples having a new baby move into better neighbourhoods.
Keywords: 330